2019
DOI: 10.1111/gfs.12426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tannin extracts on protein degradation during ensiling of ryegrass or lucerne

Abstract: Eleven laboratory‐scale trials were undertaken in different years where ryegrass (Lolium perenne L.) or lucerne (Medicago sativa L.) were ensiled with different concentrations of tannin extracts (quebracho, Schinopsis balansae Engl., mimosa, Acacia mearnsii DE WILD.), and the effects on protein degradation were assessed. The dry‐matter (DM) content in grass silages ranged between 186 and 469 g/kg and in lucerne silages between 187 and 503 g/kg. Tannin extract, either quebracho or mimosa, was applied at 0–30 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Ensiling is a dynamic process accompanied by enzyme and microbial activities [ 34 ]. Here, one of the most important biochemical reactions is proteolysis, which transforms proteins into NPN (such as small peptides, free amino acid, and AN) under the activities of microorganisms and proteases [ 43 ]. The conversion of TP to NPN (PA fraction) reduces the N utilization in ruminants, further increasing urinary and fecal N losses and causing environmental pollution [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ensiling is a dynamic process accompanied by enzyme and microbial activities [ 34 ]. Here, one of the most important biochemical reactions is proteolysis, which transforms proteins into NPN (such as small peptides, free amino acid, and AN) under the activities of microorganisms and proteases [ 43 ]. The conversion of TP to NPN (PA fraction) reduces the N utilization in ruminants, further increasing urinary and fecal N losses and causing environmental pollution [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the formation of ammonia reduces the pH drop in the ensiling process, which is essential to produce deterioration-resistant silage (Jayanegara et al, 2018). Condensed tannins (CT) appear to have potential as protein protective agents during ensiling of forage plants due to their great affinity for amino acids, proteins and polysaccharides, which can slow down the decomposition of protein during ensiling (Martens et al, 2019), and lead the reduction of losses by effluent and gases (Nascimento et al, 2017;Syahniar et al, 2018). CT are inexpensive and easy to obtain, as they are widely distributed in forage plants adapted to the semi-arid (Silanikove et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of CT levels above 5% DM can inhibit the animal's intake and reduce the digestibility of the silage (Martens et al, 2019), which will directly affect animal performance. However, Nascimento et al (2017) observed that the addition of 7.5% CT in silages of plants of the Manihot genus at 28 and 56 days of opening the silos did not affect the silage quality, promoting increases in the DM content and in the concentration of organic acids.…”
Section: Introductionmentioning
confidence: 99%
“…The current growing competition between human food production and animal feed resources calls for new animal feed alternatives that do not compromise human food supply. There is a special interest in research on non-conventional forage species that can be offered as hay or silage all year round, particularly at times of feed scarcity as in case of drought or floods (1,2,3) . Tithonia diversifolia (TD) is a non-leguminous species that is widely distributed in humid and sub-humid areas of America, Africa, Asia, and in regions close to the tropical and subtropical belts (4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…Also, low quality tropical forages constitute some of the main factors that limit the development of livestock production systems due to poor animal performance. This is the reason for which high-quality excessive forage produced during the rainy season should be preserved as silage (2,8) . Considering that TD shows high natural distribution in tropical countries, this underutilized plant can contribute to livestock production if its foliage is conserved as silage (5,9,10) .…”
Section: Introductionmentioning
confidence: 99%